Persepsi Suami dan Istri Terkait Beban Ganda Istri dalam Keluarga Buruh Tambak di Desa Pangkah Wetan Kecamatan Ujungpangkah Kabupaten Gresik - Mei Zuliawati; Oksiana Jatiningsih (Universitas Negeri Surabaya (Unesa), 2023)
Double burden becomes an important problem for a wife, especially from a poor family. The wife must participate in meeting the needs of the family, thereby creating incompetence and compulsion in a wife. This study aims to reveal the perception of husband and wife related to double burden wife in the family of aquaculture workers. The theory used in this study is the perception theory of Mc Shane and Von Glinow, explaining that receiving information through surroundings requires consideration, a way to categorize information, and how to interpret it through the knowledge possessed. This research was conducted in Pangkah Wetan Village, Ujungpangkah District, Gresik Regency, using a qualitative research approach with a descriptive design. The informants of this study consisted of eight people from four married couples who were selected purposively based on those from aquaculture workers' families aged thirty to sixty years. The focus of this study is the husband and wife's view of the double burden experienced by the wife in the household. Data were collected through observations made every day regarding the time of activities carried out by husband and wife and in-depth interviews. For data validity, source and technique triangulation was used. The results showed that the perceptions of husbands and wives had several differences. Families who have a low economy receive a double burden and require their wives to work. Meanwhile, families who have enough economy allow their wives to work so that other needs are met. Keywords: Husband, Wife, Perception, Double Burden, Pond Workers Double burden becomes an important problem for a wife, especially from a poor family. The wife must participate in meeting the needs of the family, thereby creating incompetence and compulsion in a wife. This study aims to reveal the perception of husband and wife related to double burden wife in the family of aquaculture workers. The theory used in this study is the perception theory of Mc Shane and Von Glinow, explaining that receiving information through surroundings requires consideration, a way to categorize information, and how to interpret it through the knowledge possessed. This research was conducted in Pangkah Wetan Village, Ujungpangkah District, Gresik Regency, using a qualitative research approach with a descriptive design. The informants of this study consisted of eight people from four married couples who were selected purposively based on those from aquaculture workers' families aged thirty to sixty years. The focus of this study is the husband and wife's view of the double burden experienced by the wife in the household. Data were collected through observations made every day regarding the time of activities carried out by husband and wife and in-depth interviews. For data validity, source and technique triangulation was used. The results showed that the perceptions of husbands and wives had several differences. Families who have a low economy receive a double burden and require their wives to work. Meanwhile, families who have enough economy allow their wives to work so that other needs are met. Keywords: Husband, Wife, Perception, Double Burden, Pond Workers